Impact of polio vaccines (oral polio vaccine - OPV or inactivated polio vaccine - IPV) on rotavirus vaccine-associated intussusception - Camila Cristina Martini Rodrigues; Eder Gatti Fernandes; Paulo Piva dos Santos; Renato Yoshio Eguti; Antonio Carlos Pedroso-; Gisela Tunes da Silva; Ana Marli Christovam Sartori (Taylor & Francis Group, 2022)
Although safe, rotavirus vaccines have been associated with increased intussusception risk. In Brazil, after the oral human rotavirus vaccine (OHRV) introduction in the childhood immunization, in 2006, increased intussusception risk was identified after the second OHRV dose, whereas in other countries, higher risk was associated to the first vaccine dose. It was hypothesized that the concomitant use of oral poliovirus vaccine (OPV) in Brazil might explain this difference. In 2012, the inactivated polio vaccine (IPV) was adopted in the first two doses of Brazilian childhood immunization schedule, creating an opportunity to study the subject. Our objective was analyzing the impact of polio vaccines on rotavirus-associated intussusception. We used surveillance data on intussusception in infants living in São Paulo State. Two periods were considered: an OPV-period (March 2006 to June 2012) and an IPV-period (October 2012 to December 2017). The period from June to September 2012 were considered as transition. Self-controlled case series analysis with event-dependent exposure was performed, considering two risk periods (7 and 21 days post-vaccination). We identified 325 intussusception cases in infants reported to the surveillance systems during the study period. The statistical analysis included 221 cases that occurred within 60 days after vaccination. Overall, a higher intussusception risk was observed in the first week after vaccination for both the first (Relative Incidence [RI] = 4.3, 95%CI 2.8-6.5, p < .001) and second vaccine doses (RI = 4.2, 95%CI 2.7-6.4; p < .001). There were no statistically significant differences in intussusception risk according to the rotavirus vaccine dose and the polio vaccine (OPV or IPV) administered concomitantly.